Antibiotics related adverse drug reactions in Ethiopia - Hailye Birhane; Mathew George; Lincy Joseph; Mujahidu Islam; Damen H/Mariam; Vijender Singh (Songklanakarin Journal of Science and Technology (SJST), 2022)
Antibiotics are one of the most common drugs that can induce adverse drug reaction (ADR). A retrospective analysis was conducted using suspected antibiotic-related ADR data collected from the Ethiopian Pharmacovigilance Center over a 5-year period (2014-2019). There were a relatively large number of antibiotic-related ADRs (57.9%) containing 462 suspected drugs reported, with adults aged 18-64 (65.5%) and females (61.5%) predominating in the reported cases. Monotherapy and oral route administration were responsible for 85% and 83% of ADRs, respectively. Co-trimoxazole and amoxicillin were responsible for more than half of the reported ADRs and skin disorder was half of the affected system organ (SOC). Serious ADRs constituted 26% of all reported ADRs. The outcome of the patient showed that (44.7%) of patients were completely recovered after discontinuing the offending drug and additional intervention. The finding in this study suggests that antibiotic related ADRs are a significant health problem for patients in Ethiopia and further health facility based research is suggested.